(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This research proposes a reflection on the Ethical dimension, for the configuration of a Senticreante Biopedagogy in Colombia, it deals with the problem of disciplinary pedagogical practices that opt for the formation of subjects from rationally delimited objects of knowledge, and omit the sentient singularities of the subjects that cohabit multicultural and pluricultural landscapes. Located in the biocentric paradigm, from a transdisciplinary methodology (Endoesthetics, Auto ethnography and Creation research), this research proposes to turn towards sensitive aesthetic possibilities, as a hopeful bet for the bioethical civilizing advance in Colombia. Preliminary conclusions show the urgency of new relationships between human-nature, local-universal culture, center-periphery, school-civil society, colonial-decolonial thought.